Sexual intercourse and risk of ischaemic stroke and coronary heart disease: the Caerphilly study - Ebrahim, S (BMJ Group, 2002)
Objective: To examine the relation between frequency of sexual intercourse and risk of ischaemic stroke and coronary heart disease. Design: Cohort study with 20 year follow up. Setting: The town of Caerphilly, South Wales and five adjacent villages. Subjects: 914 men aged 45–59 years at time of recruitment in 1979 to 1983. Main outcome measures: Ischaemic stroke and coronary heart disease, all first events and fatal events. Results: Of the 914 men studied, 197 (21.5%) reported sexual intercourse less often than once a month, 231 (25.3%) reported sexual intercourse twice or more a week, and the remaining 486 (53.2%) men fell into the intermediate category. Frequency of sexual intercourse was not associated with all first ischaemic stroke events: age adjusted odds ratios (95% CI) for intermediate and low frequency of sexual intercourse of 0.61 (0.32 to 1.16) and 0.71 (0.34 to 1.49) respectively compared with the reference category of high frequency. A graded relation with fatal coronary heart disease events was observed in events recorded up to 10 years. The age adjusted relative risk (95% CI) of fatal coronary heart disease contrasting low frequency of sexual intercourse (that is, less than monthly) with the highest group (at least twice a week) was 2.80 (1.13 to 6.96, test for trend, p=0.04) which was not attenuated by adjustment for a wide range of potential confounders. Longer follow up to 20 years showed attenuation of this risk with odds of 1.69 (95% CI 0.90 to 3.20), contrasting low frequency of sexual intercourse with the highest group. Conclusions: The differential relation between frequency of sexual intercourse, stroke and coronary heart disease suggests that confounding is an unlikely explanation for the observed association with fatal coronary heart disease events. Middle aged men should be heartened to know that frequent sexual intercourse is not likely to result in a substantial increase in risk of strokes, and that some protection from fatal coronary events may be an added bonus.